Comprehensive evaluation of liver microsomal cytochrome P450 3A (CYP3A) inhibition: comparison of cynomolgus monkey and human. (3rd June 2017) - Haarhoff, Zuzana E.; Kramer, Melissa A.; Zvyaga, Tatyana A.; Zhang, Jun; Bhutani, Priyadeep; Subramanian, Murali; Rodrigues, A. David
Abstract: 1. Members of the cytochrome P450 3A (CYP3A) subfamily metabolize numerous compounds and serve as the loci of drug–drug interactions (DDIs). Because of high amino acid sequence identity with human CYP3A, the cynomolgus monkey has been proposed as a model species to support DDI risk assessment. 2. Therefore, the objective of this study was to evaluate 35 known inhibitors of human CYP3A using human (HLM) and cynomolgus monkey (CLM) liver microsomes. Midazolam was employed as substrate to generate IC50 values (concentration of inhibitor rendering 50% inhibition) in the absence and presence of a preincubation (30 mins) with NADPH. 3. In the absence of preincubation, the IC50 values generated with CLM were similar to those obtained with HLM (86% within 2-fold; 100% within 3-fold difference). However, significant differences (up to 48-fold) in preincubation IC50 were observed with 17% of the compounds (raloxifene, bergamottin, nicardipine, mibefradil, ritonavir, and diltiazem). 4. Our results indicate that in most cases the cynomolgus monkey can be a viable DDI model. However, significant species differences in time-dependent CYP3A inhibition can be observed for some compounds. In the case of raloxifene, such a difference can be ascribed to a specific CYP3A4 amino acid residue.